2022
DOI: 10.1007/s12011-022-03188-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Cadmium in Muscles of Five Freshwater Fish Species from Manzalah Lake, and Possible Human Risk Assessment of Fish Consumption (Egypt)

Heba H. Abdel-Kader,
Mohamed H. Mourad

Abstract: The Egyptian government devised a plan in 2016 to improve the unique ecological significance of northern lakes, which mentioned Manzalah Lake in the Egypt Vision 2030. In this regard, this study investigated cadmium (Cd) content in five freshwater fish species collected from Manzalah Lake in Egypt at 2018 by local fishermen. According to the findings, Clarias gariepinus recorded the highest concentration of Cd (1.40 ± 0.2 μg/g) and the lowest concentration was recorded in O. aureus (1.19 ± 0.2 μg/g). Cadmium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Only As was included in the CR calculation as it was the only MM in this study that was identified by the IARC as a carcinogen [ 58 ]. It was shown in the Table that the CR of the brackish water fish was 0, which was lower than the threshold value of indicating a negligible risk of developing cancer [ 42 , 44 ]. The CR of the marine water fish was which was also lower than the threshold value of indicating negligible risk of developing cancer [ 42 , 44 ] from the consumption of marine water fish.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only As was included in the CR calculation as it was the only MM in this study that was identified by the IARC as a carcinogen [ 58 ]. It was shown in the Table that the CR of the brackish water fish was 0, which was lower than the threshold value of indicating a negligible risk of developing cancer [ 42 , 44 ]. The CR of the marine water fish was which was also lower than the threshold value of indicating negligible risk of developing cancer [ 42 , 44 ] from the consumption of marine water fish.…”
Section: Resultsmentioning
confidence: 99%
“… where CDI is the chronic daily intake of MMs (mg kg −1 day −1 ) and SF is the slope factor (mg kg −1 day −1 ), as shown in Table 1 [ 38 ]. Cancer risk is categorized as negligible if CR < 1 × 10 −6 ; acceptable if CR is within 1 × 10 −6 –1 × 10 −4 ; high if CR is within 1 × 10 −3 –1 × 10 −1 ; and very high if CR > 1 × 10 −1 [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation